Self-standing piezoelectric nanogenerator fabrics from ZnO-doped PVDF nanofiber yarns - Borazan, Ismail; Çelik Bedeloğlu, Ayşe (John Wiley and Sons Inc, 2024)
Today a wide variety of wearable electronics are in our daily lives and their uses are increasing. The development of portable, flexible, lightweight, cost-effective, and stable devices that produce sustainable energy with renewable approaches in the field of wearable electronics, as in every field, is one of the important issues of today. According to their volume and weight, the use of nanofibers with high surface area in energy-generating devices may bring them advantages such as lightness and higher energy density. Therefore, in recent years, researchers have focused on the development of nanofiber-based nanogenerators that produce energy using mechanical energy in a sustainable and renewable way. In this paper, self-standing piezoelectric nanogenerator (PENG) fabrics were obtained by developing flexible composite poly(vinylidene fluoride) (PVDF) nanofiber yarns doped with zinc oxide (ZnO) nanoparticles at different rates to provide higher power output. It has been characterized from electromechanical, structural, and morphological aspects. The most successful self-standing PENG fabric obtained (at 5% ZnO loading) doubled the energy output of the fabric made from pure PVDF nanofiber yarn and provided a peak total power of 81 ?W and a power density of 30 ?W/cm2. The present results open up the field for the development of PVDF/ZnO-based nanomats and their use in sensors and actuators in the healthcare and engineering industries. © 2023 The Authors. Journal of Applied Polymer Science published by Wiley Periodicals LLC.
Keywords: nanofiber yarn; nanogenerator fabric; poly(vinylidene fluoride) (PVDF); self-standing piezoelectric nanogenerator